Magnetic Skyrmion Generation by Reflective Spin Wave Focusing - Yao, Xianglong; Wang, Zhenyu; Deng, Menghua; Li, Z.-X.; Zhang, Zhizhi; Cao, Yunshan; Yan, Peng (Frontiers in Physics, 2021)
We propose a method to generate magnetic skyrmions by focusing spin waves totally reflected by a curved film edge. The edge contour is derived to be parabolic and frequency-independent based on the identical magnonic path length principle. We performed micromagnetic simulations to verify our theoretical design. Under proper conditions, the reflected spin waves first converge at the focal point with the enhanced intensity leading to the emergence of magnetic droplet, which is then converted to magnetic skyrmion accompanied by a change of the topological charge. We numerically obtain the phase diagram of skyrmion generation with respect to the amplitude and frequency of the driving field. Our finding would be helpful for the designment of spintronic devices combing the advantage of skyrmionics and magnonics.